If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9u+4=-5u-6-2u
We move all terms to the left:
-9u+4-(-5u-6-2u)=0
We add all the numbers together, and all the variables
-9u-(-7u-6)+4=0
We get rid of parentheses
-9u+7u+6+4=0
We add all the numbers together, and all the variables
-2u+10=0
We move all terms containing u to the left, all other terms to the right
-2u=-10
u=-10/-2
u=+5
| 56x1.12=62.72 | | 2c-1=-1-9c | | 9m+12=4m-28 | | 2s^2+6s+7=0 | | 5w-36=27 | | -4n+1=-5n | | 4-8b=-10b-10 | | 4x-8+5x-20=180 | | 3x+2−x=11x+9 | | 3x+2−x=11x+9. | | (w+5)*w=36 | | -9d=8−8d | | 7x+34+9x+22=180 | | 7x+34+9x+22=90 | | -7−5p=-4p | | -17-3(x+9)=50 | | W+5=36/w | | 5x-10+4x-8=90 | | 3(x-7)^2=75 | | 10h+6-5h+3=5h+9 | | 6x+1=37,x= | | -6(2+4x)=84- | | 8.25s−2.375=10 | | -5v-4(-8-4v)=98 | | -2(1+6x)=82 | | 10=7+9-3c | | 113=17-8x | | 7+9=3c | | 24.3=n=125.32 | | x^{2}+7x+11=0 | | (7/4)x=28 | | 13(6x+30)=x+5(x+4)–2x |